Development of Ti–Al–V alloys for usage as single-axis knee prostheses: evaluation of mechanical, corrosion, and tribocorrosion behaviors - Pinto, B. O. [UNESP]; Torrento, J. E. [UNESP]; Grandini, C. R. [UNESP]; Galindo, E. L. [UNESP]; Pintão, C. A.F. [UNESP]; Santos, A. A. [UNESP]; Lisboa-Filho, P. N. [UNESP]; Pontes, F. M.L. [UNESP]; Correa, D. R.N. [UNESP] (Springer Nature, 2023)
Single-axis knee prosthesis is an artificial biomechanical device that provides motion to amputees without the need for assistance appliances. Besides it is mainly composed of metallic materials, the current commercial materials did not group adequate properties for long-term usage or accessible cost. This study produced and characterized Ti-(10 −x)Al-xV (x = 0, 2, and 4 wt.%) alloys for potential use as single-axis knee prostheses. The samples exhibited a gradual decrease in the density values, with proper chemical mixing of the alloying elements on the micro-scale. The phase composition exhibited a primary α phase with a minor α′ + β phase for the Ti-8Al-2V and Ti-6Al-4V samples. Due to their different atomic radius compared to Ti, the addition of alloying elements changed the cell parameters. Their selected mechanical properties (Young’s modulus, Vickers microhardness, and damping factor) performed better values than the CP-Ti grade 4. The samples also exhibited good corrosion properties against the simulated marine solution. The tribocorrosion resistance of the samples was better than the reference material, with the wear tracks composed of some tribolayers and grooves resulting from adhesive and abrasive wear. The Ti-10Al alloy displayed the best properties and estimated low cost to be used as single-axis knee prostheses.